Ionosphere Monitoring with Remote Sensing - Giannattasio, Fabio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the characterization of the physical properties of the Earth's ionosphere, contributing to unveiling the nature of several processes responsible for a plethora of space weather-related phenomena taking place in a wide range of spatial and temporal scales. This is made possible by the exploitation of a huge amount of high-quality data derived from both remote sensing and in situ facilities such as ionosondes, radars, satellites and Global Navigation Satellite Systems receivers.